2018
DOI: 10.1186/s12992-018-0440-z
|View full text |Cite
|
Sign up to set email alerts
|

Global supermarkets’ corporate social responsibility commitments to public health: a content analysis

Abstract: BackgroundSupermarkets have unprecedented political and economic power in the food system and an inherent responsibility to demonstrate good corporate citizenship via corporate social responsibility (CSR). The aim of this study was to investigate the world’s largest and most powerful supermarkets’ publically available CSR commitments to determine their potential impact on public health.MethodsThe world’s largest 100 retailers were identified using the Global Powers of Retailing report. Thirty-one supermarkets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 61 publications
2
51
0
2
Order By: Relevance
“…With regard to supermarkets, a 2018 study examining corporate social responsibility reporting of the largest 100 supermarkets globally found that whilst supermarkets had taken action to report on sustainability-related issues, there was a limited focus on nutrition and health [ 35 ]. This aligns with the findings of BIA-Obesity Australia 2018 , where supermarkets had limited disclosure around nutrition-related policies and commitments and scored low overall.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to supermarkets, a 2018 study examining corporate social responsibility reporting of the largest 100 supermarkets globally found that whilst supermarkets had taken action to report on sustainability-related issues, there was a limited focus on nutrition and health [ 35 ]. This aligns with the findings of BIA-Obesity Australia 2018 , where supermarkets had limited disclosure around nutrition-related policies and commitments and scored low overall.…”
Section: Discussionmentioning
confidence: 99%
“…Administrative support is limited (Park, Kim, You, You, Kim, et al, ; Park, Kim, You, You, & Yun, ). Therefore, a proactive management framework is needed as part of another CSR activity (Pulker et al, ) for representative distribution channels.…”
Section: Resultsmentioning
confidence: 99%
“…Some foods are harder to reformulate than others due to technical and functional roles of salt, such as its use as a preservative in many products, role in the control of yeast growth and fermentation in bread, and role in sensory and textural properties in processed meats [50]; and manufacturers of these product types may be more likely to be looking for support. Lastly, the lack of sodium targets for these processed foods at the time of these media releases meant that there was no incentive for manufacturers to reformulate other than corporate social responsibility [51]. After the VSRP campaign, in May 2020, the federal government announced the rst wave of voluntary sodium targets for manufacturers to meet by 2024, which include four VSRP targeted categories: bread, cooking sauces, crackers (not dips), and selected processed meats [52].…”
Section: Discussionmentioning
confidence: 99%